2007
DOI: 10.1007/s10750-007-0607-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal diversity of small shallow waters in river Lužnice floodplain

Abstract: To propose a concept of their mutual diversity, twenty-nine permanent shallow floodplain pools and oxbows in the river Lužnice floodplain were analysed for area, depth, shape, flooding, and shading by terrestrial vegetation, and sampled in all seasons for their water chemistry, phytoplankton composition and biomass, and zooplankton composition. The sites are regularly flooded, eutrophic, and often shaded by surrounding vegetation. Cryptophyceae, Chrysophyceae and Euglenophyceae dominated the phytoplankton, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…Similar effects in small ponds were observed, e.g. by Declerck et al (2007) and Pithart et al (2007). In contrast, effects of macrophyte photosynthesis on water quality could not be detected.…”
Section: Second Component: Agricultural Solutes Inputsupporting
confidence: 71%
“…Similar effects in small ponds were observed, e.g. by Declerck et al (2007) and Pithart et al (2007). In contrast, effects of macrophyte photosynthesis on water quality could not be detected.…”
Section: Second Component: Agricultural Solutes Inputsupporting
confidence: 71%
“…However, after the floods, the washing out effect of nutrients from the floodplain area resulted with an increase in nutrient concentrations due to the natural input and accumulation of organic matter from terrestrial vegetation. Thus, the floodplain served as a ''zone of storage and turnover of organic matter'' (Pithart et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The high levels of nutrients (especially TP) established during the limnophase indicated that the river water did not serve as a major source of nutrients as is characteristic for tropical floodplains (Nabout et al, 2006;Weilhoefer and Pan, 2007). Thus, the nutrient enrichment during potamophase can be considered as the result of the in-lake processes due to the natural input and accumulation of organic matter from terrestrial vegetation in the river-floodplain system, generally recognized as ''zones of storage and turnover of organic matter'' (Keckeis et al, 2003;Pithart et al, 2007). The appearance of dissolved oxygen demand during the usually flooded year confirmed strong organic matter degradation and interface nitrogen transformation (McCarthy et al, 2008) consequently expressed as high NO 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%